Factors predicting overall success: a review of 747 microsurgical vasovasostomies - Bolduc, Stéphane (Canadian Medical Association, 2007)
OBJECTIVES: Advances in surgical techniques have improved the outcome of microsurgical vasovasostomy (VV). We performed a retrospective analysis of surgical procedures to determine outcomes and predictors of VV success, to develop Kaplan–Meier Curves for predicting VV outcomes and to evaluate the use of α-glucosidase (AG) to predict outcomes. PATIENTS AND METHODS: We undertook a retrospective analysis of 747 modified 1-layer microsurgical VV procedures performed between 1984 and 2000. Obstructive interval, partner status, social status preoperatively and method of vasal obstruction, vasal fluid quality and sperm granuloma intraoperatively were compared with outcome results. Parameters evaluated at follow-up included semen analysis, AG concentration in ejaculate fluid and pregnancy rates. RESULTS: The overall patency rate was 86% and pregnancy rates were 33% and 53% at 1 and 2 years after primary VV, respectively. Preoperative factors associated with successful outcome and pregnancy included shorter obstructive interval and same female partner (p < 0.05). Intraoperative factors predicting success included the use of surgical clips instead of suture at vasectomy, the presence of a sperm granuloma, the presence and quality of vasal fluid, and the presence and quality of sperm in vasal fluid. Further, increased AG in the postoperative semen predicted improved patency and pregnancy outcomes. CONCLUSION: This study confirms the effectiveness of VV for vasectomized men who wish to father children. It also demonstrates that preoperative and intraoperative factors are predictive of the VV outcome. Postoperative AG is also a useful marker of patency and it appears to predict pregnancy outcome.